SOSIALISASI PENINGKATAN EKONOMI MASYARAKAT PESISIR MELALUI PENANGKAPAN DAN PENGOLAHAN RAJUNGAN BERWAWASAN LINGKUNGAN - sunarto sunarto; Mega Laksmini Syamsudin; M. Rudyansyah Ismail (Buletin SWIMP, 2022)
Warduwur Village is a coastal village located in Mundu District, Cirebon Regency. The majority of residents have a livelihood as crab fishermen. Some of the residents who catch crabs are still using environmentally friendly fishing gear. The use of fishing gear is generally because some residents do not know the rules and benefits of using environmentally friendly fishing gear. Regulations for catching crabs that are environmentally friendly are in the spotlight for the next generation because one thing has been highlighted that crabs cannot be cultivated, while crabs are the main source of income for the community. Efforts to solve these problems are carried out by community service through socialization. The series of community service activities starts from observation, assessment, action plans, and implementation of activities. The method of activity is carried out through lectures filled by the Cirebon district food security office and service lecturers. Lectures are carried out in a hybrid manner at the village hall, the community can also participate in socialization through digital platforms. The results of community service understand that the capture and processing of environmentally friendly crabs will maintain business and ecological sustainability.